Annotated record of the detailed examination of Mn deposits from U.S.N.S. Kane 1968 expedition in the Northern Atlantic ocean - F A Bowles; E A Angino; J W Hosterman; O K Galle (PANGAEA, 1971)
Five of 34 dredge hauls taken in the Atlantic Ocean recovered a material tentatively described on shipboard as a salmon-colored clay. X-ray diffraction analysis showed the clay material to consist principally of palygorskite. Occurring with the palygorskite are quartz, calcite, and dolomite. It is suggested that the palygorskite (and sepiolite) is the result of chemical precipitation brought about by the reaction of hydrothermal solutions with sea water.
Supplement to: Bowles, FA et al. (1971): Precipitation of deep-sea palygorskite and sepiolite. Earth and Planetary Science Letters, 11(1-5), 324-332, https://doi.org/10.1016/0012-821X(71)90187-7